Pengaruh belajar Aqidah Akhlak terhadap rasa karsa peserta didik di MAN 1 Kabupaten Bogor - Awaliyah, Rivia; Supriadi, Dedi; Alfaien, Noor Isna (Program Studi Magister Pendidikan Agama Islam, 2026)
This study aims to determine the influence of learning Aqidah Akhlak on the rasa karsa (emotional and volitional aspects) of students at MAN 1 Bogor Regency. The background of this research is rooted in the importance of Aqidah Akhlak learning in shaping students' faith and noble character, as reflected in their rasa karsa—which encompasses inner sensitivity and the will to act according to Islamic values. This research employed a quantitative approach using a survey method with questionnaires distributed to 100 students as the sample. Data analysis included validity and reliability tests, simple regression analysis, and t-tests. The results showed that both the learning of Aqidah Akhlak and the students’ rasa karsa levels were in the